Neurolytic blockade of the obturator nerve in the treatment of idiopatic obturator neuralgia - Ćulafić Slobodan; Spaić Milan; Zoranović Uroš; Mišović Sidor (Vojnosanitetski Pregled)
Introduction. Idiopathic obturator neuralgia is a rare chronic pain condition. It consists of pain radiating from the obturator nerve territory to the inner thigh. However, the symptomatic obturator neuralgia is commonly caused by the obturator canal bowel hernia that causes painful compressive neuropathy in more than 85% of the cases. Case report. A 61-year-old female who underwent right femoral amputation due to the occlusion of the aortofemoral vascular graft, complained of the pain characterized by its localization in the inguinal region and anterointernal side of the right inner thigh. Computer tomography and MRI findings excluded obturator canal herniation or lumbar plexopathy. A diagnosis of the obturator neuralgia was confirmed by an analgesic block of the obturator nerve. Thereafter, the neurolitic blockade of the right obturator nerve was done. The complete pain relief was achieved. Pain relief was complete in three-month follow-up period. Conclusion. Neurolitic blockade is an efficacious method in treating chronic pain caused by the idiopathic obturator neuralgia.